RIICE tool for near real time monitoring of rice area, yield and climate change impacts in Mali and spillover countries - Mathieu, Renaud; Murugesan, Deiveegan; Maunahan, Aileen; Quicho, Emma; Sataphaty, Sushree; Dossou-Yovo, Elliott Ronald; Salif, Doumba; Akpoffo, Marius; Gatti, Luca (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
Reliable and seasonally updated information on the effective rice cultivated area, forecasted, harvested yield and climate change impacts are essential requirements for governments to support decision-making related to food security, management of natural resources, agricultural productivity, and insurance. The Remote Sensing based Information for Insurance and Crops in Emerging Economies (RIICE) was calibrated and validated in Mali to provide the government with reliable rice production data at harvest time and yield losses due to climate related stresses (flood and drought) to support planning in rice development and reduce the vulnerability of smallholder rice farmers by contributing to setting up affordable insurance schemes and scaling climate resilient innovations to the most affected people. RIICE relies on the integration of Synthetic Aperture Radar (SAR) derived products such as the rice area (where), the beginning of the rice crop season (when), the Leaf Area Index (LAI) and a crop growth simulation model to provide spatially explicit forecast and estimate yield at harvest time (how much will rice yield be) and the impacts of drought and flooding (how much yield may be lost). In view of the functionalities of RIICE tool developed in Mali, national stakeholders in Cote d’Ivoire expressed the need for RIICE development for Cote d’Ivoire. Subsequently, the RIICE tool has been calibrated for irrigated rice systems in Cote d’Ivoire. In a poor and data-scarce country like Mali and Cote d'Ivoire, RIICE offers an effective alternative to conventional terrestrial methods that are time-consuming, expensive, and which result in area and yield statistics that are often questioned.